RANCANG BANGUN SISTEM E-SPORT CYBERCAFE FINDER MENGGUNAKAN METODE LBS (LOCATION BASED SERVICE) BERBASIS ANDROID - Doni Indra Sazaly Saragih; Risko Liza; TM Diansyah ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - The android mobile mapping application is very popular nowadays because it really helps people for daily activities, especially helping gamers especially to find the location of the nearest cybercafe that has qualified specifications to play eSport games, the rapid world of eSport gaming which has more international tournaments. more and more people are focusing on becoming an esport gaming athlete, every esport game requires high computer specifications in order to play it smoothly and without hindrance, this is where the role of cybercafe is, cybercafe provides high-specification computer facilities which are capable of accommodating various eSport games like Dota -2, CS:GO, PUBG, Fortnite, and others. And this application is a liaison between gamers and cybercafe locations located, this application uses the very relevant LBS method used in an application based on the mapping concept, this application is created using an android studio which is thought to be qualified to make an application that is user friendly and easy to use, besides this application also requires an internet connection because it is connected directly to google maps, navigation is very important in the operation of this application. KeyWords - cybercafe, maps, location based service, android mobile, android studio.